Penyakit Virus Serius yang Menyerang Sapi dan Kerbau: Lumpy Skin Disease - Gordon, Camelia Elizabeth (Symbiohealth, 2024)
Lumpy Skin Disease (LSD) is an infectious livestock disease caused by Lumpy Skin Disease Virus (LSDV) from the Poxyviridae family with specific signs in the form of nodules on the skin. LSD is a reportable disease, namely a disease registered by the Veterinary Authority if detected or suspected must immediately be the concern of the Veterinary Authority in accordance with national regulations (OIE Glossary) and is a zoonotic disease. The disease causes many negative impacts in various areas of life so that the introduction of LSD disease is needed especially for veterinarians and field paramedics so that information about LSD can be known properly. This article discusses LSD disease, especially the definition, epidemiology, clinical symptoms, diagnosis, pathology, risk factors, and control, so that if it can be detected, reported and responded to as early as possible by all stakeholders if an LSD incident occurs.